Evaluation Study An Automatic Capture Of Glucose Level By Using Glucose Sensor For Collecting Vital Sign Data - Awangku Jaya, Awangku Khairul Ridzwan; Syahid, S.; Azahar, Arman Hadi; Mohamed Kassim, Anuar (Penerbit Universiti Teknikal Malaysia Melaka, 2019)
Nowadays, a lot of medical equipment has been integrated with the electronic device to make medical equipment more users friendly. In this project, a device using a glucose sensor to automatically capture the biological data is developed to help the doctor to follow up the patient health information. The traditional medical equipment is to take the reading such as blood pressure, blood glucose level, temperature, and etc. manually. Normally the traditional method will have many errors occur while taking the reading like parallax error or human error. Other than that, the traditional method also consumes a lot of time when taking biological data. In this project, an innovative device is designed and developed to take the biological data in automatic way to replace the manual traditional method of taking the glucose tests. The integrated device is expected to be designed to collect the blood glucose data from the designed blood glucose measuring mechanism, that is attached on a medical checkup chair and consequently integrate them into the personal medical database that can be transmitted through a USB device to a server. The traditional method consumes too much time from collecting sample until recording data into computer and human error may occurs during data recording. Hence, time consuming is lessening and faster action can be done by nurse and medical doctor while observing the patient current health information in order to provide the most suitable treatment for the patient from time to time.